(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
Pensions’ reform in most Western, Central and Eastern European countries is one of the most important topics relevant for their future development. The main objective of this study is to assist in predicting the future of the pension scheme in Albania through actuarial projections related to demographic structure, unemployment, number of contributors and beneficiaries. Through this study, we intended to predict what would be the financial effect of two options. First, we investigate the likely outcome if Albania continues with the same scheme as currently used. Second, we investigate the likely outcome when a new contributory scheme is being implemented. The methodology used for implementing the actuarial model is based on the construction of the population projections using the RUP system (Rural Urban Projection), a system developed by the Census Bureau of the United States of America, while the economic performance forecasts, i.e.: GDP, inflation rate, unemployment rate or expected indexation of wages and pensions, are be sourced by the Albanian Ministry of Finance and the International Monetary Fund. The study concludes and recommends some of the steps for reforming the pension scheme in Albania based on the experience of other countries and the likely financial effect to the state budget in case of the implementation of the new scheme. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.